Critical Thinking Processes in Numeracy Tasks among Primary School Students with High Mathematics Anxiety - Dian Kusmaharti; Via Yustitia; Hanim Faizah; Siti Maryam Rohimah; Luluk Faridah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates the influence of mathematics anxiety on the critical thinking processes of primary school students when solving numeracy tasks. Using a qualitative case study design, data were collected through written responses and follow-up interviews with students categorized according to their levels of mathematics anxiety. Analysis focused on three indicators of critical thinking: clarification, strategy, and inference. The findings show that students with high mathematics anxiety typically demonstrated the ability to extract key information from problem statements and diagrams, demonstrating strength in clarification. However, their ability to formulate strategies and provide justified inferences was limited, as they often relied on rote recall, omitted calculation steps, and expressed uncertainty about their answers. These patterns show how anxiety specifically hampers the ability to perform calculations and make confident decisions, even when students demonstrate basic comprehension. The study underscores the need for pedagogical approaches that simultaneously develop numeracy skills and address affective barriers, thereby supporting students’ capacity to engage in reasoning and problem solving more effectively.